Reversible photochromism in ⟨110⟩ oriented layered halide perovskite - Kanwat, Anil (2022)
Extending halide perovskites' optoelectronic properties to stimuli-responsive chromism enables switchable optoelectronics, information display, and smart window applications. Here, we demonstrate a band gap tunability (chromism) via crystal structure transformation from three-dimensional FAPbBr3 to a ⟨110⟩ oriented FAn+2PbnBr3n+2 structure using a mono-halide/cation composition (FA/Pb) tuning. Furthermore, we illustrate reversible photochromism in halide perovskite by modulating the intermediate n phase in the FAn+2PbnBr3n+2 structure, enabling greater control of the optical band gap and luminescence of a ⟨110⟩ oriented mono-halide/cation perovskite. Proton transfer reaction-mass spectroscopy carried out to precisely quantify the decomposition product reveals that the organic solvent in the film is a key contributor to the structural transformation and, therefore, the chromism in the ⟨110⟩ structure. These intermediate n phases (2 ≤ n ≤ ∞) stabilize in metastable states in the FAn+2PbnBr3n+2 system, which is accessible via strain or optical or thermal input. The structure reversibility in the ⟨110⟩ perovskite allowed us to demonstrate a class of photochromic sensors capable of self-adaptation to lighting.